Pengaruh Model Discovery Learning Terhadap Pemahaman Konsep IPA di Kelas V SD - Utami Dinur Ismi; Harmawati; Haerudin (Jurnal Sekolah Dasar, 2020)
The aims of this research to found the Discovery Learning system affect of Science concept understanding in fifth grade of SDN Pinayungan I District Telukjambe Timur. The approach of this research is is quantitative. The subject of this research are the fifth grade semester 2 students of SDN Pinayungan I in period 2018/2019. By choosing two of the four classes as a research sample, this is VD as the experiment class and VC class as the control class, which amounted to 27 students in each class. 5 question essay tests which uses as the instrument of eliciting data. The data analysis is to try the hypothesis with statistic descriptive calculation that is category medium score and category deviation. The result of understanding Science consept validity test showed that the 5 question is valid. The results of reliability test obtained a value of 0.76. From the hypothesis test, showed significant affect between before and after apply the Discovery Learning system of Science concept understanding level. This obtained rcount as big as 0.791 ≥ rtabel 0.344 with significant 0.05 and n = 27 then the hypothesis are accepted. From this research indicates that affect of Science concept understanding with apply Discovery Learning system in fifth grade that obtain a significant affect.